2000
DOI: 10.1007/978-3-642-57556-3
|View full text |Cite
|
Sign up to set email alerts
|

Ökonomische Theorie der Familienpolitik

Abstract: Dieses Werk ist urheberrechtlich geschützt. Die dadurch begründeten Rechte, insbesondere die der Übersetzung, des Nachdrucks, des Vortrags, der Entnahme von Abbildungen und Tabellen, der Funksendung, der Mikroverfilmung oder der Vervielfältigung auf anderen Wegen und der Speicherung in Datenverarbeitungsanlagen, bleiben, auch bei nur auszugsweiser Verwertung, vorbehalten. Eine Vervielfältigung dieses Werkes oder von Teilen dieses Werkes ist auch im Einzelfall nur in den Grenzen der gesetzlichen Bestimmungen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…There are only a few empirical studies that analyze the effects of a reform of household taxation on labor supply of married women and on the income distribution in Germany (Wagenhals and Kraus 1998, Althammer 2000, Spahn, Kaiser and Kassella 1992, Gustafsson 1992. All of these studies are based on the German Socio-Economic Panel Study (GSOEP) and estimate standard labor supply models for married couples, where the focus is on the labor supply response of wives to a shift from the system of income splitting to separate taxation.…”
Section: Labor Supply Effects -Previous Empirical Studies For Germanymentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a few empirical studies that analyze the effects of a reform of household taxation on labor supply of married women and on the income distribution in Germany (Wagenhals and Kraus 1998, Althammer 2000, Spahn, Kaiser and Kassella 1992, Gustafsson 1992. All of these studies are based on the German Socio-Economic Panel Study (GSOEP) and estimate standard labor supply models for married couples, where the focus is on the labor supply response of wives to a shift from the system of income splitting to separate taxation.…”
Section: Labor Supply Effects -Previous Empirical Studies For Germanymentioning
confidence: 99%
“…As in Althammer (2000), these policy variations are set up to be neutral in tax revenues. Female labor supply is modelled as a linear function of marginal net wage rate and other net household income.…”
Section: Labor Supply Effects -Previous Empirical Studies For Germanymentioning
confidence: 99%
“…Only in the case of families with three or more children, is the French system more favorable for a majority of households than the current German system. Regarding work incentives, previous research has shown that introducing a family splitting system in Germany would not lead to a marked increase of the labor force participation of married women (see Althammer 2000, Beblo et al 2004). This is not surprising, since even under a family tax splitting system, incomes of all earners within a family are taxed at the same marginal tax rate, which always leads to negative work incentives for secondary earners (see, among others, Wrede 2003 andApps andRees 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We analyze the effects of these reforms on the income distribution and on work incentives on the basis of a behavioral micro-simulation model which integrates an empirical household labor supply model into a detailed tax-benefit model based on the German Socio-1 Althammer (2000) simulates a family splitting reform that -besides introducing child splitting factors -cuts the sum of splitting factors for married spouses from 2 to 1.5. Beblo et al (2005), on the other hand, simulate a family tax splitting following the French example that becomes effective, however, only for families who are better off under this reform scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Dieser Ansatz wurde vielfach um Aspekte wie Interaktion von Qualität und Quantität (Becker & Lewis 1973), dynastischer Nutzen (Becker & Barro 1986), Lohnrelation zwischen Mann und Frau (u. a. Butz & Ward 1979), Timing von Geburten und Skaleneffekte (Cigno 1991) sowie familienpolitische Maßnahmen (Althammer 2000, Zimmermann 1984b) weiterentwickelt. Auch gibt es ökonomische Theorien, die der mit der Kohortengröße verbundenen Arbeitsmarktkonkurrenz (Easterlin 1961(Easterlin , 1978(Easterlin , 1980, Kapitalintensität (Gabor & Weil 1996) und Realzinsen (Becker & Barro 1988) Erklärungskraft zuschreiben (siehe 3.10, 3.11).…”
Section: Der Zweite Geburtenrückgang Als Eigenständiges Phänomenunclassified